Cytokine profile in canine immune-mediated polyarthritis and osteoarthritis - Hegemann, N.; Wondimu, A.; Kohn, B.; Brunnberg, L.; Schmidt, M. F. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The purpose of this study was to determine the cytokine profile in 21 dogs with canine immune-mediated polyarthritis (IMA) and 15 dogs with osteoarthritis (OA) caused by cranial cruciate ligament rupture (CCLR). The mRNA expression of interleukin (IL)-1α, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, IL-18, interferon (IFN)-γ, transforming growth factor (TGF)-β, and tumour necrosis factor (TNF)-α were analysed in synovial fluid by semi-quantitative RT-PCR, while TNF-α protein was determined by L929 cytotoxicity assay. The frequency of lymphocytes was analysed using FACScan. Both disorders reveal a similar cytokine expression pattern, except for significant lower IL-1β expression in OA. Th1 cytokines IL-2 and IFN-γ were detected, while IL-4 was nearly absent in IMA and OA. Furthermore, the bioassay demonstrates a significantly higher production of TNF-α in synovial fluid of dogs with IMA, compared to dogs with OA (p< 0.05). The frequency of CD4+, CD8+ and MHC class II+ cells was relatively higher in synovial fluids compared to peripheral blood in IMA. These findings reveal that the difference between the cytokine pattern of canine IMA and OA seems to be rather quantitative than qualitative. Both joint disorders show predominance of pro-inflammatory cytokines and absence of TH2 cytokine expression, indicating the potential of IL-4 for a gene therapeutic approach.
Keywords: Dog; cytokine profile; immune-mediated polyarthritis; osteoarthritis